PENGEMBANGAN BAHAN AJAR KIMIA BERPIKIR KRITIS PADA MATERI PERUBAHAN DAN PEMISAHAN MATERI UNTUK SISWA SMK TEKNIK BANGUNAN - Rita Sianturi; Mukhamad Nurhadi; Aman S.Panggabean (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop critical-thinking-oriented chemistry teaching materials for the topics of material changes and mixture separation for students of the Building Engineering Program in vocational high schools. The research employed a Research and Development (R&D) method using Borg & Gall’s model, involving material experts, language experts, practitioners, as well as teachers and students as trial participants. The developed teaching materials include contextual construction-related phenomena, analytical activities, discussions, and reflective tasks to stimulate students’ critical thinking skills. Validation results show that the materials are highly valid, with scores of 98.75% from material experts, 87.5% from language experts, and 87.95% from practitioners. Practicality tests reveal student responses at 77% (practical) and teacher responses at 88% (highly practical). These findings indicate that the critical-thinking-oriented chemistry teaching materials are relevant, feasible, and practical for learning in vocational schools, specifically in the Building Engineering Program. The materials enhance conceptual understanding and foster critical thinking skills through real-world construction contexts.